Some Socioeconomic Factors and Lifestyle Habits Influencing the Prevalence of Obesity among Adolescent Male Students in the Hail Region of Saudi Arabia - Awfa Y. Alazzeh; Eyad M. AlShammari; Majdi M. Smadi; Firas S. Azzeh; Bandar T. AlShammari; Suneetha Epuru; Shahidah Banu; Rafia Bano; Shadi Sulaiman; Jerold C. Alcantara; Syed A. Ashraf; Samir Qiblawi (MDPI AG, 2018)
A cross-sectional study was conducted to investigate the effect of some socioeconomic factors and lifestyle habits on the prevalence of obesity among adolescent male students in the Hail region, Saudi Arabia. A questionnaire was filled by 1495 male adolescents distributed among 12 schools in the Hail region. Body weight and height were taken, and the Z-score of students was measured using Anthroplus software with a cutoff 1-2 and +2 standard deviations to determine overweight and obesity, respectively. The study revealed that 21.3% of students were overweight and 27% were obese, respectively. There was a negative association between family size of >8 and obesity (OR: 0.68, CI: 0.48-0.92, p = 0.05). Family income of <5000 SR was negatively associated with obesity (OR: 0.59, CI: 0.36-0.97, p = 0.03). Whether a subject's mother worked (odds ratio (OR): 1.43, confidence interval CI: 1.03-1.99, p = 0.03) as well as the subject's mother's education-whether she can read and write, has a middle school degree, or has done postsecondary studies-were positively associated with obesity. Exercise, regardless of the duration, was negatively associated with obesity. In addition, sleeping <6 h/day had a positive association with obesity. Conclusion: a >8 family size and a low family income were negatively associated with obesity, while having an educated and working mother was positively associated with obesity.